Design, Synthesis, and Organocatalytic Activity of N‐Heterocyclic Carbenes Functionalized with Hydrogen‐Bond Donors in Enantioselective Reactions of Homoenolates. Issue 36 (15th November 2013) - Nawaz, Faisal; Zaghouani, Mehdi; Bonne, Damien; Chuzel, Olivier; Rodriguez, Jean; Coquerel, Yoann
Abstract: A focused library of chiral imidazolinium salts functionalized with urea‐type hydrogen‐bond donor moieties has been prepared from the chiral pool. The corresponding N‐heterocyclic carbenes were evaluated as organocatalysts in three enantioselective reactions involving homoenolate intermediates generated from enals. The catalysts proved competent in enantioselective cyclopentannulation and γ‐lactonization reactions, a premiere for imidazoline‐based NHCs. This work conveys some new ideas and knowledge on the concepts of bifunctional enantioselective organocatalysis applied to NHCs. Abstract : Chiral 1, 3‐imidazolin‐2‐ylidene NHCs functionalized with urea‐type hydrogen‐bond donors have been evaluated as organocatalysts in enantioselective reactions of homoenolates. Some unprecedented levels of enantioselectivity have been obtained.